PEMASARAN DIGITAL PENGEMBANGAN USAHA HANDMADE AKSESORIS “SARACA” - Faizatul, Zelyn; Mashudi, Mashudi (Universitas Sahid, 2023)
E-commerce is a marketing or advertising medium that is very close to the target market. Society now relies on digital communication. This is an opportunity for business people to make e-commerce as a medium to attract consumer attention to the products they want to offer. This is the background for the conduct of Digital Marketing research on Saraca Handmade Accessories Business Development. The purpose of this study is to find out in depth about how digital marketing strategies and management by these business people. The research was conducted using descriptive qualitative methods. The research data used is primary data obtained through in-depth interviews with handmade accessories business owners